Factors influencing online purchase intention in online brand - Hasan, Haslinda; Harun, Amran; Zainal Rashid, Mohd Shaffran (Trans Stellar Journal Publication, 2015)
This study investigated factors influencing online brand purchase intention. The aim of the study is to test the relationships between brand name, perceived ease of use and perceived usefulness (IV) and online purchase intention (DV). Consumers aged 21 years old and have had experiences in purchasing products or services online were selected as the sample of the study. A total of 175 sets of valid and usable questionnaires, were collected for further data analysis. The findings revealed that the factor, the perceived ease of use makes the largest contribution in influencing consumers’ online purchase intention in online brand. The website brand name was also found to be the essential factor for consumers’ intention to purchase online.